Studies on Physico-chemical Properties and Fatty Acid Composition of Kakri (Cucumis momordica L.) Seeds Oil From The Arid Zone of Rajasthan - RATHORE, SHASHI; SHERWANI, M.R.K. (Asian Journal of Chemistry, 2010)
In present study, physico-chemical characteristics and fatty acids composition of kakri (Cucumis momordica L.) seeds oil were determined. Oil contents, protein contents, moisture content, free fatty acid, saponification values, iodine values, refractive index, specific gravity, unsaponifiable matter and fatty acids composition of oils extracted from seeds were determined. The oil content was 22.22 %. The oil consists of 68.16 % of unsaturated fatty acids and the main fatty acids are linoleic acid (52.63 %), palmitic acid (21.05 %), oleic acid (14.33 %), stearic acid (10.79 %) and linolenic acid (1.20 %). The other characteristics of the kakri seeds oil are approximately as follows: protein contents, 16.40 %; moisture content, 7.0 %; free fatty acid, 3.6 %; saponification value, 126; refractive index, 1.479; specific gravity, 0.914 g/cm3; unsaponifiable matter, 2.5 % and iodine value, 176.